Prayer Time Calculation Method Using Global Positioning System (GPS) - Zulkifli, Husin; Mohd Najmuddin, Mohd Hassan (Malaysian Invention and Design Society (MINDS), 2010)
En. Zulkifli Husin and his team won bronze at ITEX 2007, 18th - 20th May 2007 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.